Mapping theoretical and methodological perspectives for understanding speech interface interactions - Harte, Naomi (My University, 2019)
The use of speech as an interaction modality has grown considerably through the integration of Intelligent Personal Assistants (IPAs- e.g. Siri, Google Assistant) into smartphones and voice based devices (e.g. Amazon Echo). However, there remain significant gaps in using theoretical frameworks to understand user behaviours and choices and how they may applied to specific speech interface interactions. This part-day multidisciplinary workshop aims to critically map out and evaluate theoretical frameworks and methodological approaches across a number of disciplines and establish directions for new paradigms in understanding speech interface user behaviour. In doing so, we will bring together participants from HCI and other speech related domains to establish a cohesive, diverse and collaborative community of researchers from academia and industry with interest in exploring theoretical and methodological issues in the field.
CHI EA '19 Extended Abstracts of the 2019 CHI Conference on Human Factors in Computing Systems
Keywords: Intelligent Personal Assistants (IPAs); Speech interface; Voice user interface; Theory; Method; Design